Growing use of three-part tariffs by MNOs: Understanding incentives of MNOs - Jaewon Jang; Youngsun Kwon (International Telecommunications Society (ITS), 2014)
This paper sets up a microeconomics model to analyze the market outcomes of two-part tariffs and three-part tariffs. Specifically, this paper compare the market outcomes of a single two-part tariffs to a single three-part tariffs under the assumptions that the market structure is monopolistic, there is no demand uncertainty, and demand curve is a linear straight line. The results show that a single two-part tariffs and a single three-part tariffs bring forth the same market outcomes except lump-sum fees. The lump-sum fees of the three-part tariffs are the lump-sum fees of the two-part tariffs plus the revenue loss caused by an allowance (free volume provided to customers). Therefore, according to this result, the monopolist has no reason to prefer three-part tariffs to two-part tariffs. However, if customers do not use up all allowance or there is demand uncertainty, three-part tariffs can generate more profits to the monopolist than two-part tariffs. Moreover, three-part tariffs can be used by the monopolist to raise lump-sum fees without losing customers and profits.
Keywords: 330; Three-part tariff; Two-part tariff; Smart phone; Allowance; Lump-sum fees